PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN AFEKTIF, KOMITMEN NORMATIF, DAN KOMITMEN KONTINUAN KARYAWAN PADA PERUSAHAAN SWASTA - Masripah Masripah, SE., M.S.Ak (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2016)
The objecive of thisÂ research is to determine the effect of job satisfaction on affective commitment, normative commitment, and continuance commitment of employees at the company. This research uses secondary data and primary data, namely the reference literature and surveys by giving questionnaires. The test results of this research to the 33 respondents indicated job satisfaction has a significant positive effect on affective commitment and continuance commitment of employees at the company. However, the research find that job satisfaction has significant negative effect on normative commitment of employees at the company. The results also proves that the factor most likely influenced by the job satisfaction of employees at the company is normative commitment, and how employers should treat their employees have contributed most compared to the salaries of employees in creating job satisfaction.ring listed in Indonesia Stock Exchange 2012-2013 period and has met the criteria established by the researchers , as many as 17 companies . The results of the analysis of this study showed that the Current Ratio and Return On Equity does not affect the Dividend Payout Ratio , while the Debt to Equity Ratio and Total Asset Turnover affect the Dividend Payout Ratio .Â